Infrastructural legacies and post-Soviet transformations in Northern Sakha (Yakutiya), Russia - Peter Schweitzer (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna); Olga Povoroznyuk (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna) (Journal of Environmental Policy & Planning, 2022)
The abstract is available here: https://uscholar.univie.ac.at/o:1628933 The abstract is available here: https://uscholar.univie.ac.at/o:1628933